Analysis of the Influence of Financial Leverage on Financial Performance at Mining, Oil and Gas Companies Listed on Indonesia Stock Exchange - Dovi Septiari; Arbi Hasbi Nasution (Journal of Applied Accounting and Taxation, 2017)
This paper aims to determine the effect of the use of debt to finance the company's operations on the performance of companies in the industry mining, oil and gas. The model used in this research is quantitative research. The samples used were 151 samples. This sample consists of companies mining, oil and gas listed on the Indonesian Stock Exchange from 2010-2014. Data analysis method used is using simple regression analysis. Research by a simple regression method with earnings per shares, net profit margin and return on equity as the dependent variable and the debt to equity ratio as independent variables. Results of this study indicate that the use of debt or debt to equity ratio does not significantly affect the company's financial performance such as earnings per shares, net profit margin and return on equity. The use of high debt to meet the company's operations are not necessarily able to improve financial performance.